Pengembangan LKPD Berbasis Proyek Terintegrasi Green Chemistry Pada Materi Hukum Dasar Kimia - Zulfa, Ria; Muntari, Muntari; Anwar, Yunita Arian Sani (Chemistry Education Practice, 2025)
This research aims to determine the feasibility of using a project-based learning (PjBL) students’ worksheet (LKPD) containing green chemistry about fundamental laws of chemistry, based on the development results in terms of validity and practicality. The green chemistry principles studied in this research are limited to Green Chemistry Principle number 1, namely the Preventive Principle. This type of research is included in research and development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The development of LKPD was declared feasible in terms of two aspects, namely validity and practicality, with a percentage result of 61% or higher. The results of the LKPD feasibility test, focusing on the validity aspect, were evaluated by three validators and yielded an average percentage of 81%, meeting very valid criteria. The practicality of the LKPD was seen from activity observations and student response questionnaires, which obtained practical results with an average percentage of 79.3%. Based on these results, the Project-Based Learning (PBL) LKPD, which incorporates green chemistry into the fundamental law, is suitable for use